PELATIHAN PERHITUNGAN TARIF RUMAH SAKIT BERDASARKAN INA CBG’S DI RUMAH SAKIT ISLAM JAKARTA - Andry Priharta; Nur Asni Gani; Teguh Pantjatmono; Rony Edward Utama; Tri Ananto; Jaharuddin Jaharuddin; Fathurachman Fathurachman (Taksasila Edukasi Insani, 2025)
Training is given to health service providers who are not financial employees at the hospital. Jakarta Islamic Hospital is one of the hospitals that is a BPJS Kesehatan provider and receives INA CBG's tariff payments determined by the Government. For this reason, all employees need to have the ability to create cost effectiveness and efficiency. The training was carried out using the method of delivering material followed by discussion between participants. Before and after the activity, a pre-test and post-test were carried out as a medium to measure the level of understanding of the participants. The results of the activity concluded that the use of INA CBG's tariffs is a financial reality that ultimately plays an important role in measuring management performance and as a basis for decision making. How this concept is used for good financial optimization of the organization, it is highly recommended for managers at all levels and all employees to have awareness and understand the basic concepts and of hospital finances that have changed in the JKN era, from fee for service to INA CBG's.Keywords: National Health Insurance, Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS) Health, Fee for Service, Indonesia Case Based Groups (INA-CBG's)